Dormancy in sunflower line A-3: The role of the pericarp - Vigliocco, Ana Edit (2017)
Sunflower (Helianthus annuus L.) can often display seed dormancy, which causes a delay for immediate sowing. The final degree of “whole seed” dormancy is determined by the contributions of the tissues that comprise it, such as, embryo, seed coat, and (or) pericarp. The sunflower dormancy can be reduced during after-ripening and by removing seed constraints. Our objective was to study how the conditions of storage and removal of the pericarp affect the level of dormancy in line A-3. Also we provide insight on the basis of the morphological characteristics of A-3 pericarp-imposed dormancy. A germination test was conducted on dry cypselas with and without pericarp, at 30 and 70 days after harvest. For histological analysis, permanent slides of pericarp crosssections were obtained. The germination percentage showed significant differences between cypselas with intact pericarp (30 days after harvest = 26%; 70 days after harvest = 77%), and cypselas without pericarp (30 days after harvest = 65%; 70 days after harvest = 96%). This indicates that the pericarp plays an important role in regulating physical dormancy in the seed of sunflower line A-3, and that its relative contribution to the dormancy level is modified during after-ripening.